Chemtrails and Covid-19: Two Faces of Evil - Whiteside, Mark; Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2022)
Chemtrails and Covid-19, two faces of Evil, threaten all life on our planet solely for political reasons. If we are to have a viable future on this planet, a critical mass of humanity must wake up to the atrocities of the ongoing chemtrail and biological operations. People must break out of their mass formation hypnosis and distractions, start to look up, and bear witness to the terrible suffering of the natural world around us. We are not separate entities from the rest of the biosphere: if the forests die, the wildlife dies, and the oceans die, we too will die. Our time is short – action is urgently needed now to salvage what remains of our natural life support systems and give our children a healthy and viable future.